Bradycardia Without Hypertension: Is It a Common Clinical Presentation of Ventriculoperitoneal Shunt Malfunction in Pediatric Patients?. Issue 12 (December 2021) - Marmor, Itay; Carbell, Gary; Koplowitz, Jake; Roth, Jonathan; Shimoni, Nir; Constantini, Shlomo; Rimon, Ayelet; Glatstein, Miguel Marcelo
Abstract : Background: Mechanical shunting of cerebrospinal fluid is an effective treatment for hydrocephalus. Some studies suggest that bradycardia without hypertension may also be observed in ventriculoperitoneal (VP) shunt malfunction; however, in our experience, this is not a common presenting sign. Objective: The aim of this study was to evaluate whether bradycardia without hypertension was a common sign in patients presenting to the pediatric emergency department (ED) with a VP shunt malfunction. Methods: A retrospective observational study, from May 2006 to April 2015, which included a random sample of children admitted to the ED with clinical features suggestive of possible VP shunt malfunction. Control patients were defined as those who arrived at our ED with suspected VP shunt malfunction that was later ruled out on further workup. Results: A total of 65 patients were included in this study. A significantly greater number of patients with a confirmed shunt pathology presented with vomiting ( P = 0.01) and lethargy/apathy ( P = 0.01). In the control group, a significantly greater number of patients presented with fever ( P = 0.004) and seizures ( P = 0.02). The number of patients presenting with bradycardia was not significantly different between the shunt pathology and control groups ( P > 0.05). Conclusions: Bradycardia is not a common presentation in patients with VP shunt malfunction. Bradycardia is often recognized as a significant sign; however, it is one of the last presenting signs. Educating patients about the early signs must be considered as part of the treatment for VP shunt malfunction.